Evaluating online problem-based learning as a way forward post COVID-19 pandemic - Lye, An Jie (2022)
Introduction: The outbreak of the COVID-19 pandemic left medical schools with no choice but to move physical teaching and learning sessions to online platforms. Following the changes, problem-based learning (PBL) sessions were conducted online to facilitate students’ learning. Although online PBL seemed to be an appropriate solution during the pandemic, it remains unknown whether this teaching and learning mode shall be continued after the pandemic. Therefore, this study aimed to investigate the acceptance of online PBL among medical students by comparing their PBL learning experiences at the commencement of online PBL and after one year of the implementation. The findings provided some evidence for medical schools before making the next decision. Methods: This study was carried out at the Faculty of Medicine, Universiti Malaya. A 12-item questionnaire with a 5-point Likert scale was developed and validated among pre-clinical medical students. Based on the principal component analysis and internal consistency test, the questionnaire was valid and reliable. The self-administered questionnaire was distributed with students using Google Form twice (1st time = the commence of online PBL; 2nd time = after a year of the implementation of online PBL). Students were given two weeks to complete and submit their responses. Data were analysed by using the Mann-Whitney U test to compare the online PBL learning experiences of medical students at two different points in time. Results: Two hundred and seventy students (response rate = 80%) completed the questionnaire. Based on the findings, online PBL was perceived to be effective. Students’ online PBL experiences improved after a year of participating in online PBL sessions. They were able to receive and understand the information from online PBL sessions. Despite the favourable responses, students also expressed their concerns on passing clinical examinations and the mastery of content. Conclusion: Online PBL is an acceptable solution during the pandemic, medical schools might consider continuing its implementation post-pandemic, subject to further research.